2020
DOI: 10.1038/s41416-020-01107-w
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and its therapeutic possibilities in paediatric cancers

Abstract: In tumours, hypoxia—a condition in which the demand for oxygen is higher than its availability—is well known to be associated with reduced sensitivity to radiotherapy and chemotherapy, and with immunosuppression. The consequences of hypoxia on tumour biology and patient outcomes have therefore led to the investigation of strategies that can alleviate hypoxia in cancer cells, with the aim of sensitising cells to treatments. An alternative therapeutic approach involves the design of prodrugs that are activated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 174 publications
0
29
0
Order By: Relevance
“…This increasing interest in targeting the tumor microenvironment has made tumor hypoxia one the most promising targets of therapy in several types of tumors [ 30 ], including NB [ 29 ]. Meanwhile, hypoxia-targeted treatment strategies have progressed into clinical trials [ 4 ], although many of these approaches have not been successfully implemented in the clinic, largely because trial designs have not included methods to identify and select patients with hypoxic tumors prior to enrolment. Therefore, the necessity to include reliable biomarkers that could be predictive of a positive response to hypoxia-targeted treatment strategies in future clinical trials has been pointed out [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increasing interest in targeting the tumor microenvironment has made tumor hypoxia one the most promising targets of therapy in several types of tumors [ 30 ], including NB [ 29 ]. Meanwhile, hypoxia-targeted treatment strategies have progressed into clinical trials [ 4 ], although many of these approaches have not been successfully implemented in the clinic, largely because trial designs have not included methods to identify and select patients with hypoxic tumors prior to enrolment. Therefore, the necessity to include reliable biomarkers that could be predictive of a positive response to hypoxia-targeted treatment strategies in future clinical trials has been pointed out [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, hypoxia-targeted treatment strategies have progressed into clinical trials [ 4 ], although many of these approaches have not been successfully implemented in the clinic, largely because trial designs have not included methods to identify and select patients with hypoxic tumors prior to enrolment. Therefore, the necessity to include reliable biomarkers that could be predictive of a positive response to hypoxia-targeted treatment strategies in future clinical trials has been pointed out [ 4 ]. We previously designed a biology-driven approach to assess the hypoxic status of NB primary tumors from the analysis of the gene expression profile of 11 distinct NB cell lines cultured under hypoxic and normoxic conditions for 18 h, deriving a robust 62 probesets signature (NB-hypo).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Bhoopathi et al demonstrated that the Secreted Protein Acidic and Rich in Cysteine (SPARC) overexpression in neuroectodermal tumours induces autophagymediated apoptosis and enhances the efficacy of radiation therapy [70,71]. However, when combined with chemotherapy instead of radiation therapy, SPARC expression induces chemoresistance; particularly, it suppresses cisplatin sensitivity in MB cells due to the increased levels of autophagy, acting as a tumour survival mechanism [72].…”
Section: Relationship Between Autophagy and Mb Subtypesmentioning
confidence: 99%
“…For example, soft tissue sarcomas (STSs) are prone to forming large and highly hypoxic tumors, leading to increased risk of metastasis [6,7]. Therefore, investigating combination therapies to target multiple molecular pathways involved in metastasis, such as hypoxia, could potentially improve patient prognosis [8]. The study of hypoxia and its implications on radioresistance have been a topic of interest in fundamental, pre-clinical and clinical research, culminating in 2019 with the Nobel Prize in Physiology or Medicine [9].…”
Section: Introductionmentioning
confidence: 99%